(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This study highlights the importance attributed to the bankruptcy administrative authority in the Insolvency Act. In the new act such authority is heterogeneous and its members being from professional bodies, one of its disadvantages being the absence of a list of duties of its members, from various professional backgrounds, as well as defencelessness regarding the nature of the post.